Men And Matriculture Among the Ho-Chunks / Paul Radin, ed. The Autobiography of a Winnebago Indian. University of California Publications in American Archaeology and Ethnology, vol. 16, no. 7. Berkeley: University of California Press, 1920. / Nancy Oestreich Lurie, ed. Mountain Wolf Woman, Sister of Crashing Thunder: The Autobiography of a Winnebago Indian. Ann Arbor: University of Michigan Press, 1961. - Jung, Patrick J. (Matrix, 2025)
Patrick J. Jung compares and contrasts classic autobiographies of two Ho-Chunk (Winnebago) siblings from the twentieth century: Paul Radin, ed., The Autobiography of a Winnebago Indian (1920) and Nancy Oestreich Lurie, ed., Mountain Wolf Woman, Sister of Crashing Thunder: The Autobiography of a Winnebago Indian (1961).